Self-Actualization In Charlotte Bronte's Jane Eyre Novel (1847): An Humanistic Psychological Approach - Irmawati, Leni (2012)
This study analyzes Self-Actualization in Charlotte Bronte's Jane Eyre viewed from An Humanistic Approach. The objectives of the study are to reveal the aspects of self-actualization in Jane Eyre and to unveil the motivations of self-actualization, which happenin Jane Eyre and to know the impacts of Self-actualization as reflected in Jane Eyre. This study is a literary study which can be categorized into a qualitative study. In this study the writer uses two data sources namely primary and secondary data sources. The primary data source and the object of the study is the novel Jane Eyre itself, meanwhile the secondary one is any literature related with this study. The data is collected by means of documentation and it analyzed based on An Humanistic Psychological Approach. Based on the analysis, the writer draws the following conclusions. First, the literary creation is a meaningful response of the author toward social reality where the author lives. Second, in Jane Eyre, Charlotte Bronte proposes her criticism by using the social background of England in nineteenth century. The last, Charlotte Bronte considers that love is not merely involving all the emotions or the passions, but also moral as a society norm. Moral is an essential element in human's life in the relation with the feeling of love. Human being as a social creature in this life had to apply moral value in facing a good and bad thing, something that must be done or must not be.